Políticas de formação docente do Projeto Escola Cabana: dilemas e desafios da implementação do Programa de Formação Continuada - FERREIRA, Diana Lemes (2005)
This hereby research is on Educational Public Policies of Docent Graduation and studies the continued graduation of docents who have been integrating Escola Cabana Political Pedagogical Project, in Belém, Pará, from 1997 through 2004. It aims to analyze political bids of docent continued graduation policies in the context of contemporary educative reforms and of the aforesaid Projects. More specifically, this research aims to: a)identifying/analyzing the concepts of continued graduation present to Belém Municipalitys educational policy on the period 1997-2004; b) Interpreting teachers role in the process of definition/implementation of Belém Municipalitys continued graduation policies; c) Identifying/characterizing contributions from the Continued Graduation Program for the consolidation of Escola Cabana Project; d) Indicating challenges/dilemmas motivated by the educational policy under study. Methodological route charac terizef a study of case which was developed in a school belonging po Municipal Chain. Aiming to achieve targets,one did analysis of SEMECS official documents contents, and of spontaneous interviews granted from eight docents of a municipal school and from three managers of the educational policy under research (collaborators), what allowed articulat the following cathegories of analyis: contradiction and participation. This research testifies docent continued graduation as the key-point for consolidating the Project under study, although it faces dilemmas and challenges in the sense of organizing formations in a more continuous way, approximating focus to schools realities, in the search of rescuing more consistently the teacher as historical subject of educative process.